DESAIN DAN PERHITUNGAN BODY KAPAL ATAU HULL STRUCTURE PEMBERSIH SAMPAH DI PANTAI - Padlan Padlan; Trisno Susilo (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
This garbage cleaning ship is a new building design that functions as a garbage cleaning beach with a size of a ship length of 12, 4m wide and 2m high. The design of this garbage cleaning vessel is a solution to help cleaning and transporting waste along the coast in general in accordance with the Karimun district government program. Based on the results of calculations on the construction design of the garbage cleaning vessel body, the body or hull of the garbage cleaning vessel, weighs 19,766 tons and is designed to lift ± 20 tons of wet garbage. This garbage cleaning vessel has a height of 0.401 m empty ship and is loaded with a load of 0.800 m. For the design of the thickness of the plate on the Deck Plate, Shell Plate and bottom plate from the calculation found the thickness of the plate 8 mm and for the transverse stability value of the ship the value of KM 2.86 m, KG 1 m, KB 0.2 m while the stability value extends the ship KM value 24 m, KG 1 m, KB 0.2 m.